A kinematic comparison of the overhand throw and tennis serve in tennis players: How similar are they really? - Reid, M.; Giblin, G.; Whiteside, D. (Journal of Sports Sciences, 2015)
Tennis coaches often use the fundamental throwing skill as a training tool to develop the service action. However, recent skill acquisition literature questions the efficacy of non-specific training drills for developing complex sporting movements. Thus, this study examined the mechanical analogy of the throw and the tennis serve at three different levels of development. A 500 Hz, 22-camera VICON MX motion capture system recorded 28 elite female tennis players (prepubescent (n = 10), pubescent (n = 10), adult (n = 8)) as they performed flat serves and overhand throws. Two-way ANOVAs with repeated measures and partial correlations (controlling for group) assessed the strength and nature of the mechanical associations between the tasks. Preparatory mechanics were similar between the two tasks, while during propulsion, peak trunk twist and elbow extension velocities were significantly higher in the throw, yet the peak shoulder internal rotation and wrist flexion angular velocities were significantly greater in the serve. Furthermore, all of these peak angular velocities occurred significantly earlier in the serve. Ultimately, although the throw may help to prime transverse trunk kinematics in the serve, mechanics in the two skills appear less similar than many coaches seem to believe. Practitioners should, therefore, be aware that the throw appears less useful for priming the specific arm kinematics and temporal phasing that typifies the tennis serve.